Eruptive angioma. Fibromatosis. - Bonifazi, E.; Longo, F.; Tarantino, G.; Ciampo, L.; Berloco, A.; De Roma, M.R.; Conca, R. (European Journal of Pediatric Dermatology, 2000)
Eruptive angioma (EA) is a benign proliferation of angiopoietic tissue rapidly growing in a few weeks till causing erosion of the epidermis and bleeding. In the past its most frequent synonym was pyogenic granuloma, whereas the most recent term of “lobular capillary hemangioma” was proposed by Mills et Al. (17). Since 1982, starting from the report of Mulliken and Glowacki (18) there were some attempts of classification of lesions, which in the past had been all included in the chapter of angioma. These attempts are laudable because they try to introduce pathological and functional criteria, in contrast with the previous classification using exclusively clinical criteria. In a new classification (24) all the previously known angiomatous lesions are classified into the categories as follows: hamartomas, malformations, dilatations of preexisting vessels, and proliferations, the latter being in turn subdivided in hyperplasias, benign neoplasms and malignant neoplasms. Unfortunately, the borders between the various entities, for instance between hyperplasia and benign neoplasm or even between benign and malignant neoplasm (23) are not always well defined as it would be necessary for a classification, because nature does not jump.(...).